Avaliação das características de superfície e formação de biofilmes em materiais odontológicos tratados em plasmas de HMDSO - Wady, Amanda Fucci [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Dental materials act as substrates for the adhesion of microorganisms, and consequently, for biofilm development. Given that the surface characteristics of materials may interfere in the initial adhesion, changes in these characteristics may inhibit or reduce the adhesion of bacteria and fungi, thus preventing the development of diseases. Another aspect to consider is that, in the oral cavity, surfaces are covered with saliva, forming a thin film referred to as acquired salivary pellicle. In order to simulate oral conditions, in vitro studies have used preconditioning in human saliva before biofilm formation. Thus, the aim of this study was to evaluate the effect of plasma polymerized films on the surface characteristics of dental materials (acrylic resin, titanium and zirconia), as well as on the biofilm formation on these materials, with and without preconditioning in human saliva. For this purpose, the monomer hexamethyldisiloxane HMDSO was used as precursor in the PECVD (Plasma Enhanced Chemical Vapor Deposition) process. Deposition parameters were varied to produce a range of films with hydrophobic or hydrophilic characteristics. Specimens of each material without film deposition were used as controls. Characterization of the films was performed by Fourier Transformed infrared spectroscopy (FTIR), scanning electron microscopy (SEM), contact angle measurements and surface free energy, X-ray photoelectron spectroscopy (XPS), and profilometry. To evaluate biofilm formation, half of the test specimens (10 × 2 mm) of the experimental and control groups were stored in previously prepared 16 human saliva and afterwards incubated with 1 × 107 cells/mL of both Candida albicans (for acrylic resin) and Porphyromonas gingivalis (for titanium and zirconia). Samples without preconditioning in saliva were also incubated in the respective microorganisms... (Complete abstract electronic access below)
Keywords: Candida albicans; Saliva; Biofilme; Prótese dentária